1999
DOI: 10.1557/proc-564-321
|View full text |Cite
|
Sign up to set email alerts
|

Integration of PECVD Tungsten Nitride as a Barrier Layer for Copper Metallization

Abstract: Amorphous tungsten nitride (WNx) is a promising diffusion barrier for extending Cu metallization beyond 0.18 μm. This study evaluates the barrier performance, adhesion, and step coverage of PECVD WN 0.5 integrated with a CVD Cu seed layer. The WN0.5 films exhibit amorphous structure with 33% bottom and side-wall step coverage in 0.14 μm wide structures with 9:1 aspect ratio. The potential of 50 Å WN0.5 as an effective Cu barrier is shown by the absence of Secco etch-pits in the Si substrate after a 30 min anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…[15][16][17] One motivation for exploring the tungsten derivatives is their potential applica-tion as single-source precursors for chemical vapor deposition (CVD) or atomic layer deposition (ALD) of tungsten nitride (WN x ) and tungsten carbonitride (WN x C y ), 18,19 materials of interest to the semiconductor industry as diffusion barriers in copper metallization schemes. [20][21][22][23][24][25][26][27] Preparing the hydrazido complexes provides an alternative to the addition of hydrazine derivatives into the carrier gas during deposition of metal nitride films, a process that has been reported to lower the deposition temperature of TiN films significantly because of the high reducing power of hydrazines toward high-valent transition metals. [28][29][30] In particular, it has been demonstrated that diorganohydrazido(2-) titanium complexes serve as precursors for the deposition of titanium nitride films.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] One motivation for exploring the tungsten derivatives is their potential applica-tion as single-source precursors for chemical vapor deposition (CVD) or atomic layer deposition (ALD) of tungsten nitride (WN x ) and tungsten carbonitride (WN x C y ), 18,19 materials of interest to the semiconductor industry as diffusion barriers in copper metallization schemes. [20][21][22][23][24][25][26][27] Preparing the hydrazido complexes provides an alternative to the addition of hydrazine derivatives into the carrier gas during deposition of metal nitride films, a process that has been reported to lower the deposition temperature of TiN films significantly because of the high reducing power of hydrazines toward high-valent transition metals. [28][29][30] In particular, it has been demonstrated that diorganohydrazido(2-) titanium complexes serve as precursors for the deposition of titanium nitride films.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problem of copper contamination, thin films acting as diffusion barriers are used. , Besides having good resistance to diffusion, barrier films should be structurally and thermally stable, exhibit good adhesion to both copper and dielectric layers, be nonreactive with copper, have low resistivity, and be resistant to thermal and mechanical stresses. Tungsten nitride (WN x ) and tungsten carbonitride (WN x C y ) are promising candidates for barrier materials based on these criteria. Recently, we reported metal−organic chemical vapor deposition (MOCVD) growth of WN x and WN x C y thin films using a series of related single source precursors: the phenylimido complex Cl 4 (CH 3 CN)W(NPh) ( 1 ), the isopropylimido complex Cl 4 (CH 3 CN)W(N i Pr) ( 2 ), and the allylimido complex Cl 4 (CH 3 CN)W(NC 3 H 5 ) ( 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Excess nitrogen present in these materials can migrate to grain boundaries, helping to block these potential diffusion pathways through repulsive Cu−N interactions. , An example of a refractory metal nitride that has found applications in IC technology is tantalum nitride (TaN), which has been used as a barrier material for intermediate and upper level wiring in some IC devices . Another metal nitride that is a promising candidate for thin film barrier materials is tungsten nitride (WN x ). This material has the additional advantages of increased adhesion to copper, potential seedless copper electrodeposition, and facile processing (e.g., more efficient chemical mechanical polishing) . In addition to these binary nitrides, the ternary material tungsten carbonitride (WN x C y ) has also shown promise for diffusion barrier applications.…”
Section: Introductionmentioning
confidence: 99%
“…4 Another metal nitride that is a promising candidate for thin film barrier materials is tungsten nitride (WN x ). [5][6][7] This material has the additional advantages of increased adhesion to copper, 8 potential seedless copper electrodeposition, [9][10][11] and facile processing (e.g., more efficient chemical mechanical polishing). 12 In addition to these binary nitrides, the ternary material tungsten carbonitride (WN x C y ) has also shown promise for diffusion barrier applications.…”
Section: Introductionmentioning
confidence: 99%